Combined Compliance Calculation Method of the Flexure Hinge with Variable Cross Section and Its Verification - Guan Lixin; Liu Qingling (Jixie chuandong)
The flexure hinge is the most basic compliant structure,the compliance is the most important performance parameter. The combined compliance method is proposed fully based upon the structure characteristic of the flexure hinge. The structure characteristics of the right circle,corner filleted and elliptical flexure hinge are fully analyzed,half of the flexure hinge is selected as the research object and the reasonable integral variable is set,the compliance formulas for calculating the half of the flexure hinge are obtained. By combining the different kinds of the half flexure hinge,the combined compliance formulas for calculating the compliance of the 12 kinds flexure hinges are obtained. The compliance of the right circle flexure hinge,right circle elliptical hybrid flexure hinge and right circle corner filled half hybrid flexure hinge are calculated and analyzed with the combined compliance formulas,literatures and the finite element method. By contrasting the calculation results,the correctness and validity of the combined compliance method are verified.